Risk Management Assistance in the Clothing and Medical Equipment Business: Pendampingan Manajemen Resiko pada Usaha Pakaian dan Perlengkapan Medis PT. Lestari Dini Tunggul - Diana, Diana; Hakim, Luqman; Hananto, Djoko (Universitas Muhammadiyah Sidoarjo, 2022)
Every effort made by humans, either alone or in groups as outlined in an organization or company, has the goal of getting results in the form of profits. The process that is carried out is certainly not free from risks. By being aware of the risk in the activity process, it is necessary to know through the risk identification process to the handling of the identified risks. PT. Lestari Dini Tunggul which is located in Jagakarsa area, South Jakarta is a company that started as a family business that produces medical clothing and factories, of course, wants the company to continue to run and grow and produce good results for other stakeholders. Therefore, the community service team on this occasion helped to provide assistance regarding the implementation of risk management. The method used is Participatory Rural Appraisal (PRS) which allows partners to actively participate in activities from problem identification to the end of the activity. The material presented in the mentoring activity is an understanding of Operational Risk, Human Resources and Finance. The results of the mentoring show that qualitatively partners gain additional knowledge, understanding, and insight about Risk Management. So that in carrying out their activities they are more careful and help each other in carrying out their work processes. Furthermore, it can be concluded that this assistance in implementing Risk Management can increase knowledge, understanding and insight for all employees of PT. Lestari Dini Tunggul.